Understanding the limited protectiveness of Si-rich passive film on Fe-based shape memory stainless steels in highly oxidizing media - Silva, R.; Vacchi, G.S.; Passos, J.G.C.; Hammer, P. [UNESP]; Gomes, J.A.C.P.; Rovere, C.A.D. (Elsevier, 2025)
Fe–Mn–Si–Cr–Ni-(Co) shape memory stainless steels (SMSSs) are smart, low-cost materials that offer good mechanical properties and corrosion resistance and are suitable for use in oxidizing environments due to their elevated Si content, which helps suppress intergranular corrosion commonly observed in conventional austenitic stainless steels such as 304L, under oxidizing conditions. However, their corrosion resistance in highly oxidizing media, such as those found in spent fuel reprocessing, is not yet fully understood. This study investigates two SMSS formulations and compares their electrochemical corrosion and passive film characteristics with SS 304L in 6 M and 11.5 M HNO3 solutions, relevant for nuclear fuel reprocessing. All alloys exhibited spontaneous passivation, with stable passive films formed on SS 304L and SMSS B, while film stability on SMSS A decreased with increasing HNO3 concentration. Despite their lower Cr content, the SMSSs exhibited good passivation and slightly higher transpassive breakdown potentials than SS 304L, which suffered from intergranular corrosion. In contrast, the SMSSs exhibited generalized corrosion. The high protection of the passive films formed on the SMSSs is mainly attributed to their high Si content (72–85 at.%) in the form of SiO2, highlighting their potential, especially SMSS B, for applications in highly oxidizing environments. The findings show that although Si improves corrosion resistance in oxidizing media, its protective effect is limited in the absence of Cr. A synergistic combination of Si and Cr in the passive film is essential to ensure the stability of the oxide layer under aggressive conditions.